A Generalized Tunneling Formula for Quantum Device Modeling. Issue 1 (1998) - Lake, R.; Klimeck, G.; Bowen, R. C.; Jovanovic, D.; Sotirelis, P.; Frensley, W. R.
Abstract : The generalized tunneling formula with the simple model for the broadening in the contacts gives surprisingly good results for the majority of RTD structures. It is just as fast as the standard coherent tunneling simulators and much more versatile. It is easily generalized to multi-band and multidimensional models. The multi-band generalization of the theory and the effect of the optical potential are described.